Education and Training for the Fourth Industrial Revolution - Georg Spoettl; Vidmantas Tūtlys (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
Within the context of the 4th Industrial Revolution as an overall paradigm change, organization and work processes must switch together with automation following and real-time control. This applies to the contents of labor and to the interaction and connection between human and technology. Up to this point, there are only a few empirical studies about how digitized, decentralized and closely connected production system with "Cyber-Physical-Systems" change the task and and competence profiles in the workplace. One outcome will be that intelligent workpieces will manage their way into production themselves. Depending on the implementation level of Industry 4.0 in companies, vocational education and training for the workforce is highly relevant and the vocational systems have to respond to the needs and expectations of the new technological challenges. Successful reactions of the vocational systems towards the 4th Industrial Revolution have to focus on curriculum development, teacher training and training of highly skilled workers. Approaches to fulfill these requirements will be discussed in this paper.